Altered zygotic gene expression caused by sperm with Tdrd6 variants disrupts early embryonic development - Zhijie Hu; Yuqi Zhang; Renfei Cai; Qiuju Chen; Haiyan Guo; Danjun Li; Weidong Lin; Hongxi He; Haibo Wu; Yali Liu; Bin Li; Qianwen Xi; et al. (MedComm)
Abstract The precise mechanisms behind early embryonic arrest due to sperm‐related factors and the most effective strategies are not yet fully understood. Here, we present two cases of male infertility linked to novel TDRD6 variants, associated with oligoasthenoteratozoospermia (OAT) and early embryonic arrest. To investigate the underlying mechanisms and promising therapeutic approaches, Tdrd6 knock‐in and knock‐out mice were generated. The Tdrd6 variant male mice demonstrated OAT and embryonic arrest, mirroring the clinical observations of our patients. Sperm from both affected individuals and mice exhibited aberrant localization of phospholipase C zeta and oocyte activation deficiency (OAD). The application of artificial oocyte activation (AOA) effectively overcame the infertility caused by the variants, facilitating successful pregnancies and live births in both human and mice. Additionally, our research revealed that OAD influences the expression of multitude of genes at the 2‐pronuclear (2PN) stage, with the Mos gene playing a pivotal role in early embryonic arrest. The injection of Mos mRNA can mitigate this arrest. To our knowledge, this is the first study to show that sperm‐related OAD affects gene expression at the 2PN stage and elucidate how AOA overcomes male factor‐derived embryonic arrest, enabling successful pregnancies and live births.